2018
DOI: 10.1192/bja.2018.28
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and the diagnosis of preclinical dementia

Abstract: SUMMARYAlzheimer's disease pathology accumulates years before the onset of clinical symptoms and has been termed ‘preclinical dementia’. Biomarkers have been developed to detect this pathology – namely, brain amyloid deposition and markers of neurodegeneration. In this article we describe these biomarkers and review the evidence for their clinical use in predicting risk both in the cognitively ‘normal’ and in those who already have established cognitive decline. We also discuss the limitations and ethical cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…SAPPβ is a product of APP amyloidogenic processing, marking a critical step towards Aβ generation (Perneczky 2011). Increased CSF sAPPβ have previously correlated to Aβ peptides in AD (Lewczuk, 2010;Gabelle, 2010). As shown in the meta-analysis, CSF sAPP was significantly higher in AD compared to FTD, and intriguingly, a consequent study by the Perneczky group found sAPP was also higher in AD than FTD in plasma samples (Perneczky, 2013).…”
Section: Novel Indicators Of Amyloid Pathologymentioning
confidence: 99%
“…SAPPβ is a product of APP amyloidogenic processing, marking a critical step towards Aβ generation (Perneczky 2011). Increased CSF sAPPβ have previously correlated to Aβ peptides in AD (Lewczuk, 2010;Gabelle, 2010). As shown in the meta-analysis, CSF sAPP was significantly higher in AD compared to FTD, and intriguingly, a consequent study by the Perneczky group found sAPP was also higher in AD than FTD in plasma samples (Perneczky, 2013).…”
Section: Novel Indicators Of Amyloid Pathologymentioning
confidence: 99%
“…But investigators can identify pathophysiological findings such as amyloid-β deposition in the brain that are indicative of an increased risk of progression to clinical stages of dementia. 14 Conducting clinical trials on individuals at preclinical stages of dementia is promising as this population, unlike people at clinical stages of dementia, are generally more able to engage with researchers and provide informed consent. 15 Also, such clinical trials create new opportunities for investigating disease-modifying agents at earlier stages of dementia.…”
Section: Increasing the Recruitment Of People At Preclinical Stages Dementiamentioning
confidence: 99%
“…Alzheimer’s disease is considered a continuum with three phases: the preclinical stage characterized by normal cognitive ability, the prodromal stage characterized by mild cognitive impairment (MCI), and, ultimately, clinically apparent dementia ( Jack et al, 2018 ; Lilford and Hughes, 2018 ; Vermunt et al, 2019 ). The current dementia diagnosis due to AD requires a combination of clinical, neuropsychology, and biomarker measurements.…”
Section: Introductionmentioning
confidence: 99%